Porównanie ciepła spalania i wartości opałowej szyszek wybranych gatunków drzew leśnych - Aniszewska, Monika; Gendek, Arkadiusz (Leśne Prace Badawcze, 2014)
Every year, scaling plants buy (up to tens of tons) cones which needs to be peeled. After the process of scaling, the cones themselves are waste, which is partly sold. The problem of waste disposal is especially severe in plants where the processing is performed by electrically-powered scaling cabinets, but the problem does not apply to facilities where pellets are burned to produce heat. We examined the heat of combustion and calorific value of the residues from scaling plants that can be used in the production of refined wood fuels. The residues consist of the empty cones of pine, spruce, larch as well as husks and stems of silver fir. Additionally, we conducted measurements of the heat of combustion for wood and cones of each species and compared them to their respective calorific values The results revealed that the average calorific value of the cones is in the range 17.81–19.86 MJ/kg. Our work showed that empty cones have a significantly higher calorific value and heat of combustion than the wood of spruce, larch and fir. In the case of pine, cones and wood did not differ significantly. These results led us to the conclusions that empty de-scaled cones can be utilized as a valuable primary solid fuel or fuel additive for the production of refined products for the local market. Due to the low annual production of cones in comparison to other materials such as sawdust and wood chips, pine cones should be used as a supplement, to enrich fuels of inferior quality by enhancing their energetic properties.